Making a Living: How Middle-Class Couples in Warsaw Start and Practice a Household - Olcoń-Kubicka, Marta; Halawa, Mateusz (Kultura i Społeczeństwo, 2018)
This article is a study of the domestic monetary and financial life of young middle-class couples in Warsaw, Poland, and its suburbs. We use ethnographic evidence presented as case studies to illuminate the practices in which our interlocutors actively appropriate, mobilize, and transform money and finance to pursue moral visions of the good life. The article focuses on the household understood in processual terms of ongoing negotiations between moral and market dimensions. The first section is focused on the ways in which young couples perform relational work aimed at achieving or maintaining moral order. Couples match the diverse possible uses of money at home to their changing notions of the kind of couple they are or wish to become. The second section proceeds from the observation of a widening gap between rising middle-class aspirations and economic possibilities in contemporary Poland and explores the practices of negotiating various forms of assistance from parental households. The third and final section argues that the incursion of technologies into domestic life means that artifacts like software or digital banking increasingly materialize and mediate morality and thus actively contribute to the shaping of the household as a project of a good life.